Biventricular performance index of the fetal heart - Sosa-Olavarría, Alberto (2022)
Objectives: To propose a biventricular performance index based on the average valuesof the duration of the cardiac cycle of each of the ventricles, to determine the variableincluded in the study with the most significant statistical correlation, to establishreference values that allow the work of each ventricle to be identified according to thisvariable, and to obtain a balanced biventricular output index. Methodology: Prospectiveand cross-sectional study in fetuses of 168 pregnant women, in pregnancies between16 and 38 weeks without maternal-fetal pathologies. Flow velocity waves were obtainedfrom both atrioventricular valves and the total systole-diastole cycle time was calculatedin milliseconds for each valve. Averages, standard deviation, and Z-score were calculatedof the systolic-diastolic time for each ventricle and the individual ventricular performanceindex (VPI) were calculated by dividing the value obtained by the fetal heart rate (FHR).The average value of both was obtained and this, when divided by the heart rate, made itpossible to obtain the biventricular performance index (BPI) to establish the correlationbetween this, the fetal heart rate and gestational age. Results: Systolic-diastolic timevalues in milliseconds for the right ventricle were 420.8 (SD ±28.3) and for the leftventricle 418.8 (SD ±26.3), with no statistically significant differences (p<0.371). Thecorrelation with the FHR was negative for both ventricles: (-0.491 and -0.553; p<0.05). Themean biventricular time was 418.37 ms (±20.59) and the correlation with gestational agewas 0.48 (p<0.05); the correlation with FHR was negative, -0.50 (p<0.05).The BPI showedvalues of 2.8 (extremes 2.4 (P5) and 3.4 (P95)). The correlation between BPI and FHR was0.78 (p<0.05) and of lesser degree with gestational age (0.27; p<0.05). Conclusions: Itwas demonstrated that the systolic-diastolic times of each ventricle did not differ fromeach other and were negatively correlated with fetal heart rate. It was shown that it ispossible to evaluate the fetal cardiac cycle of each ventricle by means of the ventricularperformance index as well as to qualify with the biventricular performance index thecombined cardiac output as balanced.